2016
DOI: 10.3324/haematol.2015.139410
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing unravels the genetics of refractory/relapsed T-cell acute lymphoblastic leukemia. Prognostic and therapeutic implications

Abstract: Despite therapeutic improvements, a sizable number of patients with T-cell acute lymphoblastic leukemia still have a poor outcome. To unravel the genomic background associated with refractoriness, we evaluated the transcriptome of 19 cases of refractory/early relapsed T-cell acute lymphoblastic leukemia (discovery cohort) by performing RNA-sequencing on diagnostic material. The incidence and prognostic impact of the most frequently mutated pathways were validated by Sanger sequencing on genomic DNA from diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 49 publications
1
41
2
Order By: Relevance
“…Therefore, this small number of patients prevented us from studying a prognostic impact of NRAS/KRAS and PTEN mutations within the favorable NOTCH1 mutant group that was described previously in primary adult T-ALL. 5,17 However, it is worth noting that NRAS/KRAS and PTEN mutations were absent from the most favorable NOTCH1/FBXW7 double mutant group of T-ALL relapse patients (Figure 1). TP53 mutation and/or deletion was associated with exceptionally poor outcome in relapsed T-ALL in this study, as all patients suffered a second event and died (pEFS: 0.00±0.00 vs. 0.261±0.052; P=0.051; Figure 2B).…”
Section: 9mentioning
confidence: 99%
“…Therefore, this small number of patients prevented us from studying a prognostic impact of NRAS/KRAS and PTEN mutations within the favorable NOTCH1 mutant group that was described previously in primary adult T-ALL. 5,17 However, it is worth noting that NRAS/KRAS and PTEN mutations were absent from the most favorable NOTCH1/FBXW7 double mutant group of T-ALL relapse patients (Figure 1). TP53 mutation and/or deletion was associated with exceptionally poor outcome in relapsed T-ALL in this study, as all patients suffered a second event and died (pEFS: 0.00±0.00 vs. 0.261±0.052; P=0.051; Figure 2B).…”
Section: 9mentioning
confidence: 99%
“…In jawed vertebrates, triplication of a common ancestral TET gene led to three different TET paralogs, and a subsequent chromosomal inversion split TET2 gene into two segments encoding catalytic domain and CXXC domain, respectively [43, 45, 46]. Thus, the ancestral CXXC domain of TET2 is now separately encoded by a neighboring gene named IDAX (also known as CXXC4).…”
Section: Characteristics Of Tet Family Proteinsmentioning
confidence: 99%
“…Development of targeted therapies that inhibit pathways exploited by T-ALL to augment proliferation and survival may improve outcomes while also minimizing systemic toxicity. Prior studies involving RNA or whole genome sequencing of T-ALL samples identified the JAK/STAT pathway (32)(33)(34) and the BCL2 pathway (15) as dysregulated in these leukemias.…”
Section: Discussionmentioning
confidence: 99%